Exploring The Need for Reflective Journal as Assessmentas-Learning in A Government LMS: A Study of BPOM Employees - Kurniati, Kiki; Rejekiningsih, Triana; Sumaryati, Sri (Proceedings International Conference on Education Innovation and Social Science, 2025)
The advancement of digital learning in government institutions calls for assessment models that go beyond summative testing and foster self-regulated learning. These preliminary needs analysis investigates the perceptions and learning needs of employees at the National Agency of Drug and Food Control (BPOM) regarding the development of a reflective journal as an assessment-as-learning feature within the LMS IDEAS. Using a quantitative approach, the study involved 85 active LMS users who responded to an online questionnaire. The results indicate that while current assessments such as pre- and post-tests are perceived as clear and relevant, they are considered insufficient in promoting key aspects of self-regulated learning- namely self-monitoring, evaluation, and adaptation. Respondents expressed strong needs for additional features such as personalized feedback, structured reflection tools, and mechanisms that connect learning with workplace practices. These findings suggest that integrating a reflective journal with guided prompts and flexible formats into the LMS has the potential to enhance autonomous learning and support continuous professional development among civil servants.